W. E. Graham and Sons Quarry, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 1-28-64 p. 1.
W. E. Graham and Sons Quarry, 1964. The quarry was located on Germanton Road.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth